2012
DOI: 10.2478/v10101-012-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological gender of women taking up typically masculine sports activity

Abstract: SummaryStudy aim: To examine which gender scheme is used by women who take up stereotypically masculine sports activity and to obtain an answer to the question of whether these subjects achieve higher results on the masculinity scale and lower results in femininity than women who practise other sports and women who do not take up any sports activity. Do women who practise masculine sports achieve a higher sports class and self-evaluate their results better if they identify with a masculine image? Material and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…This dependence seems particularly important in relation to disciplines typically considered masculine, such as soccer, boxing, judo, wrestling, weightlifting, or combat sports. Studies confirm that women who practice sports typical for men more often possess androgynous and masculine psychological features than feminine or undetermined [10]. Our study revealed that women who practice yoga are more often characterized by feminine features compared to women taking part in other kinds of group physical activities, where androgynous gender predominates.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This dependence seems particularly important in relation to disciplines typically considered masculine, such as soccer, boxing, judo, wrestling, weightlifting, or combat sports. Studies confirm that women who practice sports typical for men more often possess androgynous and masculine psychological features than feminine or undetermined [10]. Our study revealed that women who practice yoga are more often characterized by feminine features compared to women taking part in other kinds of group physical activities, where androgynous gender predominates.…”
Section: Discussionsupporting
confidence: 78%
“…The research by Pacut [19] demonstrated that the majority of female soccer players (considered a masculine sport) were androgynous, while in a group of women practicing synchronous swimming and gymnastics (typically a feminine sport) the majority were psychologically feminine. Moreover, Burdzicka-Wołowik [10] showed that androgynous women predominate among women who train gymnastics, swimming, or basketball. Starzomska and Kowalczyk [20] revealed that androgynous women are especially interested in sport, regardless of the discipline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Burdzicka-Wołowik [72] suggests that there is the least amount of androgynous women among those who do not do any sports and the most among those who practice sports. The same is the case for cross-sex typed women.…”
Section: Health Practicesmentioning
confidence: 99%
“…Scientist researched studied 60 post-puberty girls in sports: boxing, judo, wrestling, gymnastics, basketball determined the dominance of the androgen type [5,6].…”
mentioning
confidence: 99%